2004
DOI: 10.1007/s10526-004-5278-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of winter wheat as a potential relay crop for enhancing biological control of cotton aphids

Abstract: A 2-year study was conducted to evaluate the role of winter wheat, Triticum aestivum L., as a potential relay crop to conserve arthropod natural enemies and suppress cotton aphids, Aphis gossypii Glover, in seedling cotton. The results suggested that the natural enemies that moved from the adjacent wheat fields to cotton fields with the maturity and harvest of wheat could keep the cotton aphid population at the edges (0-4 m) of cotton fields under the action threshold of 100 aphids/m 2 . Data also suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…Accordingly, A. gifuensis strongly parasitized the aphids on the tobacco plants in the intercropped fields, and aphid density decreased. These results are similar to the findings of Men et al () and Lai et al (). Men et al () reported that the densities of cotton aphid enemies increased in response to intercropping seedling cotton with winter wheat, and Lai et al () reported that the densities of A. gifuensis increased in tobacco fields in response to intercropping with garlic.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, A. gifuensis strongly parasitized the aphids on the tobacco plants in the intercropped fields, and aphid density decreased. These results are similar to the findings of Men et al () and Lai et al (). Men et al () reported that the densities of cotton aphid enemies increased in response to intercropping seedling cotton with winter wheat, and Lai et al () reported that the densities of A. gifuensis increased in tobacco fields in response to intercropping with garlic.…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to the findings of Men et al () and Lai et al (). Men et al () reported that the densities of cotton aphid enemies increased in response to intercropping seedling cotton with winter wheat, and Lai et al () reported that the densities of A. gifuensis increased in tobacco fields in response to intercropping with garlic. Third, disadvantageous microclimate conditions (concerning, e.g., temperature, humidity, light conditions, or odorants) for the development of aphids and virus diseases may have been caused by intercropping, leading to decreases in green peach aphid densities and/or virus disease incidence.…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, much effort has been directed toward managing the secondary pest complex in Bt cotton, and increasing the biological control effect of natural enemies is an effective strategy for overall Bt cotton management. Numerous studies suggest that the enhancement of predator abundance and diversity through increasing plant diversity exerts positive effects on pest control in many cropping systems (Andow, 1991;Parajulee et al, 1997;Parajulee & Slosser, 1999;Men et al, 2004;Gardiner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Northern China, intercropped cotton agroecosystems and mono cotton agroecosystems are very common. The effects of intercropping with wheat or of different planting dates on the physiology and yield of cotton have been extensively studied [26,27]. However, the relationship between crop diversity and productivity and key insect pests and natural enemies in different cotton agroecosystems remains unclear.…”
mentioning
confidence: 99%